Using Artifact Flow Diagrams to model Artifact Usage Anomalies - Hsu, Hwai-Jung; Wang, Feng-Jian (My University, 2009)
Workflow is a set of tasks which are systematized to achieve certain business goal(s), where the tasks run in a particular order under automatic control. Artifacts, collections of data items, are necessary for task (process) executions in a workflow. However, an execution may yield unexpected results due to improper artifact manipulation: e.g., activities miss artifact or artifact conflict occur at an activity dynamically. Therefore, the analyses on artifact usage in design phase are very important for quality insurance. This paper presents a model of artifact flow diagrams to state the artifact usage anomalies in processes transmitting artifacts based on DCDC, Distinct Control and Data Channel, model. There are four types of artifact usage anomalies identified in DCDC and the formal statement of each anomaly is described correspondingly for future study of anomaly search.
Keywords: workflow; artifact; artifact flow diagram; DCDC